2019
DOI: 10.2478/euco-2019-0028
|View full text |Cite
|
Sign up to set email alerts
|

Smart Village Development Principles and Driving Forces: The Case of Lithuania

Abstract: Traditional and emerging interest networks supported by the advancement of digital and telecommunication technologies, the growing use of bioenergy and the ability to take advantage of knowledge beneficial for local populations and business development promote strategic breakthroughs of rural communities. The paper focuses on the problem of the smart village development with respect to a sustainable rural regional development. The aim of the research is to identify the preconditions for rural area progress and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…Several studies explain the need for synergies between actor activities and policy synergies with the instruments used are resource mobilization, network areas, clusters, formal and informal associations, and are community-driven on the concept of local economic development (Atkočiūnienė & Vaznonienė, 2019;Iwara & Kilonzo, 2022;Nordberg et al, 2020) The second strategic priority is the search for other legitimate sources of financing to fund infrastructure maintenance and the provision of adequate infrastructure with a geometric mean value of 0.27718. The third strategic priority is to build the capacity of Technopark managers to provide the best training and coaching for the community, to increase social capital in the form of trust, and increase public interest in being involved in technopark programs with a geometric mean value of 0.16009 This is in line with one of the studies which revealed that to build a technopark, capable human resources are needed (Wolniak et al, 2019).…”
Section: Strategy Prioritymentioning
confidence: 99%
“…Several studies explain the need for synergies between actor activities and policy synergies with the instruments used are resource mobilization, network areas, clusters, formal and informal associations, and are community-driven on the concept of local economic development (Atkočiūnienė & Vaznonienė, 2019;Iwara & Kilonzo, 2022;Nordberg et al, 2020) The second strategic priority is the search for other legitimate sources of financing to fund infrastructure maintenance and the provision of adequate infrastructure with a geometric mean value of 0.27718. The third strategic priority is to build the capacity of Technopark managers to provide the best training and coaching for the community, to increase social capital in the form of trust, and increase public interest in being involved in technopark programs with a geometric mean value of 0.16009 This is in line with one of the studies which revealed that to build a technopark, capable human resources are needed (Wolniak et al, 2019).…”
Section: Strategy Prioritymentioning
confidence: 99%
“…Three out of five villages are known as small capitals of culture in Lithuania; 5. The villages have adopted co-creation processes: local organizations work to integrate and transform resources and competences (Atkočiūnienė and Vaznonienė, 2019). Analysing compliance with the criteria for smart villages, it was concluded that “there are high levels of community-driven activity in all the selected villages (.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…The more recent SV concept focuses on the use of modern digital technologies in rural areas and small urban communities (Van Gevelt et al, 2018). Rather than for development in public transport or citizen awareness per se, technologies in SV are more oriented towards facilitating agricultural work (Taylor, 2017), or making efficient use of available local resources (Atkočiūnienė and Vaznonienė, 2019). Rural 680/809 development through the SV concept responds to the gradually disappearing agricultural sector, underdevelopment in relation to cities, as well as social and economic disparities in the development of rural settlements (Atkočiūnienė and Vaznonienė, 2019).…”
Section: The Concept Of Smart Development Smart Projects and Barriers...mentioning
confidence: 99%
“…Rather than for development in public transport or citizen awareness per se, technologies in SV are more oriented towards facilitating agricultural work (Taylor, 2017), or making efficient use of available local resources (Atkočiūnienė and Vaznonienė, 2019). Rural 680/809 development through the SV concept responds to the gradually disappearing agricultural sector, underdevelopment in relation to cities, as well as social and economic disparities in the development of rural settlements (Atkočiūnienė and Vaznonienė, 2019). When implementing SV aspirations, smaller municipalities can benefit from cooperation with other communities and actors not only from other rural areas but also from cities located in their vicinity (European Commission, 2020).…”
Section: The Concept Of Smart Development Smart Projects and Barriers...mentioning
confidence: 99%
See 1 more Smart Citation